1990
DOI: 10.3109/08910609009140256
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Green Tea Extract on Growth of Intestinal Bacteria

Abstract: Growth responses of a variety of human intestinal bacteria to methanol extracts of green tea (Thea sinensrs L.) were investigated in vitro. Thc extracts moderately enhanced growth of some bifidobacteria strains in tests on carbon sourcecontaining media but not carbon source-free media, suggesting that bifidus factor(s) might be involved. It did not stimulate growth of clostridia, bacteroides, eubacteria or Escherichia coli. However, the extract was found to be selectively inhibitory against the growth of some … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
16
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(19 citation statements)
references
References 10 publications
3
16
0
Order By: Relevance
“…in vitro. 31 In an in vitro study conducted by Kemperman et al, 32 the antimicrobial effect of a black tea extract was analyzed by traditional culturing and qPCR, and its impact on microbial community was also assessed by PCR-DGGE and 16S rDNA measurements. 32 Several animal studies conducted in pigs 33 and in calves 34 concluded that tea polyphenols produced an enhancement in animals' intestinal microbiota.…”
Section: Hydrolysable Tannins (Ellagitannins)mentioning
confidence: 99%
“…in vitro. 31 In an in vitro study conducted by Kemperman et al, 32 the antimicrobial effect of a black tea extract was analyzed by traditional culturing and qPCR, and its impact on microbial community was also assessed by PCR-DGGE and 16S rDNA measurements. 32 Several animal studies conducted in pigs 33 and in calves 34 concluded that tea polyphenols produced an enhancement in animals' intestinal microbiota.…”
Section: Hydrolysable Tannins (Ellagitannins)mentioning
confidence: 99%
“…It was published that spice and herbal extracts such as Alpinia galanga and Rosmarinus officinalis decreased the growth of the spoilage microflora on cooked ready-to-eat-vacuumpackaged shrimp [16]. An interesting study link between the intake of the green tea and the protection from gastric cancer, and this protection could be attributed to the useful effect of the green tea on the gastric normal flora by enhancing the growth of some lactic acid bacteria and inhibiting the growth of some clostridia which could develop some gastric tract infections [3]. This raised an essential question, How are some plant principles keeps the microflora at the required range and get rid of the pathogenic microorganisms?.…”
Section: Effects Of Medicinal Plants On the Microfloramentioning
confidence: 99%
“…Antibiotics which is an effective drug against pathogenic bacteria may cause an ecological upset in the normal microflora, either quantitatively or qualitatively [2]. some studies showed that medicinal plants might have a selective inhibitory effect on some microflora [3]. Hence, medicinal plants could have advantages over the antibiotics.…”
Section: Introductionmentioning
confidence: 99%
“…Two in vitro studies on the effects of green and black tea on the inhibition of growth of different bacteria were presented (Sakanaka et al, 1990;Rasheed and Haider 1998). The Panel considers that the evidence provided in in vitro studies is not sufficient to predict the occurrence of an effect of the consumption of either catechins or tannins in Camellia sinensis (L.) Kuntze on the reduction of acid production in dental plaque.…”
Section: Reduction Of Acid Production In Dental Plaque (Id 1105 1111)mentioning
confidence: 99%
“…Three references (Ahn et al, 1990 and1991;Lee et al, 2006) related to in vitro growth inhibition studies with Camellia sinensis (L.) Kuntze methanol and ethyl acetate/water extracts. The Panel considers that the evidence provided in the in vitro studies is not sufficient to predicting an effect of consumption of catechins from green tea on decreasing potentially pathogenic intestinal microorganisms in humans.…”
Section: Decreasing Potentially Pathogenic Intestinal Microorganisms mentioning
confidence: 99%